ANALISIS SEKTOR UNGGULAN SEKTORAL DAN PENGARUHNYA TERHADAP PERTUMBUHAN SEKTOR EKONOMI DAERAH: PENDEKATAN INPUT-OUTPUT INTERREGIONAL SUMATERA BARAT, RIAU DAN JAMBI - Lukman Lukman (Indonesian Journal of Economics and Business, 2011)
The objectivity of this research is to examine and analyze: The structure of economy, regional economic of dominant sector, economic sectors are effect on the growth of regional economy and the impact on the growth of leading sectors in West Sumatra, Riau and Jambi. This research uses descriptive quantitative approach to the nature of the explanatory method of verification and used secondary data. The sectors studied were: 1) Economic Structure of the demand and supply, structure of output, structure of value added, structure of final demand (household consumption, government consumption, fixed capital formation, stock changes and exports) and Trade Structure. 2) The leading sector are: Share of output, Share of GDP, Power of distribution and degree of sensitivity, multiplier value of output, gross of value added, and labor and share of export. 3) The effect of economic sectors of regional economic growth (GDP). From government investment, private investment, employment, exports, imports, forward linkages, backward linkages, value added and value-added output.This result shows that 1) Structure of economic of the West Sumatera province is the largest based on the demand and supply of output, gross of value added and employment, another provinces are Riau and Jambi. The main structure of economic Sumatera are: food industry, beverages, and tobacco, trade, construction, other services and goods paper & printing industry. The province of Riau: hotels and restaurants, air transport, trade, other services, and livestock. The province of Jambi: coal mining, metal ore, and other excavations, food industry, beverages and tobacco, trade, construction, and land transportation. 2) The leading sector of West Sumatra in 2000 were: trade, textile industry, leather goods and footwear, other services, food industry, beverages and tobacco, rice, buildings and land transportation sector. In the 2005, trade, food industry, beverages and tobacco, services, rice, plantation sector, construction sector and land transport sector. The leading sector of Riau in 2000: oil, gas and geothermal energy, petroleum refining, transportation equipment industry, machinery and equipment, trade, plantation crops and buildings. Year 2005 plantation crops, food industry, beverages & tobacco, paper and printed material industry, commerce, fisheries, mining, oil, gas and geothermal energy, and buildings. The leading sector of Jambi in 2000: the plantation, oil, gas and geothermal energy, industry and products of wood and forest products, trade and land transportation. In the 2005, trade, plantation, food industry, beverages and tobacco, oil, gas and geothermal. 3) In West Sumatra variables, exports, imports, employment, forward linkage, backward linkages, the impact of output and gross value added impact positively on economic growth (GDP), West Sumatra. The province of Riau and Jambi, all variables are positive effect on regional economic growth (GDP) in the province.